2016
DOI: 10.1007/s00214-016-1839-3
|View full text |Cite
|
Sign up to set email alerts
|

A computational UV–Vis spectroscopic study of the chemical speciation of 2-mercaptobenzothiazole corrosion inhibitor in aqueous solution

Abstract: In order to understand the chemical speciation of 2-mercaptobenzothiazole (MBT) corrosion inhibitor as a function of pH, the electronic absorption spectra was compared with those calculated at the EOM-CCSD, TD-M06-2X and TD-B3LYP levels of theory for several different species that may result from MBT reactions in aqueous solution. The computational spectroscopic analysis was supported by the energetics of tautomerization, deprotonation, non-covalent association and ion-pair formation reactions calculated at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
0
18
0
2
Order By: Relevance
“…Density functional theory (DFT) calculations employing periodic structural models were performed here to understand the interaction of PhPh with two different aluminum surfaces and to aid the interpretation of EIS results. For comparison purposes, the interaction of 2-mercaptobenzothiazole (MBT) [14], an efficient corrosion inhibitor for aluminum alloys [15], with aluminum surface models was also considered.…”
Section: Computational Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Density functional theory (DFT) calculations employing periodic structural models were performed here to understand the interaction of PhPh with two different aluminum surfaces and to aid the interpretation of EIS results. For comparison purposes, the interaction of 2-mercaptobenzothiazole (MBT) [14], an efficient corrosion inhibitor for aluminum alloys [15], with aluminum surface models was also considered.…”
Section: Computational Sectionmentioning
confidence: 99%
“…Indeed, PhPh has a less favorable adsorption energy than MBT when deprotonated on the surface (Fig. 13), while its pK a is significantly higher [pK a (PhPh) = 9.3 [39], pK a (MBT) = 7.0 [14]], resulting in a lower capacity of PhPh to adsorb onto aluminum surfaces [E ads (PhPh deprot @Al(1 1 1)) > E ads (MBT deprot @Al (1 1 [44] have shown that an organic protective layer has an even greater insulating character than that of the oxide layer itself. Herein the simplest case of an organic protective layer was also investigated considering the adsorption of dimers with the molecules deprotonated on the surface.…”
Section: Corrosion Resistancementioning
confidence: 99%
“…Agrochemicals with 2-mercaptobenzothiazole moiety in the molecule are used as fungicides of a wide spectrum [ 75 , 76 , 77 ], herbicides [ 78 ], insecticides [ 39 , 78 , 79 ]. In industry, they are used as metal corrosion inhibitors in different media [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ], additives to lubricants [ 89 , 90 ], sorbents of trace amounts of metals, including noble metals [ 91 , 92 , 93 ] and rubber vulcanization accelerators [ 94 , 95 , 96 ].…”
Section: 2-mercaptobenzothiazolesmentioning
confidence: 99%
“…10), where MBT assumes the anionic form. In this form, the negative charge will be located between the nitrogen and the exo sulfur, which is the part of the molecule that interacts with the surface of LDH [27]. After reaction with HTMS, the XPS spectrum of the SR-LDH film (See Supplementary Materials Figure S1) presents, apart from peaks associated with N1s (E b = 399.3 eV) and S2p (E b = 163.8 eV for S1 and E b = 162.1 eV for S2) electrons, Si2p electrons with an E b = 102.3 eV corresponding to Si in silanes [28,29], indicating that functionalization has occurred near the interface.…”
Section: Figure 2 Shows the Chemical Composition At The Interface Samentioning
confidence: 99%